ADAPTASI KURIKULUM PENDIDIKAN INKLUSIF SISWA DENGAN HAMBATAN SOSIAL EMOSIONAL DI SEKOLAH DASAR - Soeratman, Suharsiwi (Perspektif Ilmu Pendidikan, 2016)
The purposes of this study are to discover the efforts of the primary school teachers to adopt the curriculum focusing on the students’ problems, curriculum adaptation, and the teachers’ effprts in solving instructional problems. The research was conducted at Semut-semut Primary School, Kelapa Dua, Depok. The findings are the IQ of the students with social-emotional problems is under the average, they have difficulties in interaction, communication, and independence. The spend between 50 % to 75 % of their time in the classroom and the remaining time they spend in Learning Support Department and 3 – 4 children learn individually. As in the curriculum adaptation, the students’ competence is developed with limitation. The children which have not been able to adopt in the class, this program is used to develop social aspect and reading, writing, and arithmetic skills as their preparation to join regular class.